2009
DOI: 10.1099/mic.0.025213-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lgt mutation on lipoprotein biosynthesis and in vitro phenotypes of Streptococcus agalactiae

Abstract: Although Streptococcus agalactiae, the group B Streptococcus, is a leading cause of invasive neonatal disease worldwide the molecular basis of its virulence is still poorly understood. To investigate the role of lipoproteins in the physiology and interaction of this pathogen with host cells, we generated a mutant S. agalactiae strain (A909DLgt) deficient in the Lgt enzyme and thus unable to lipidate lipoprotein precursors (pro-lipoproteins). The loss of pro-lipoprotein lipidation did not affect the viability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…However, an additional cross-reactive band of 100 kDa was observed in the Slgt mutant. Bray et al (2009) observed the same phenomenon and suggested that the band corresponding to the higher molecular mass represented aggregated forms of the prolipoproteins.…”
Section: F Reffuveille and Othersmentioning
confidence: 48%
See 2 more Smart Citations
“…However, an additional cross-reactive band of 100 kDa was observed in the Slgt mutant. Bray et al (2009) observed the same phenomenon and suggested that the band corresponding to the higher molecular mass represented aggregated forms of the prolipoproteins.…”
Section: F Reffuveille and Othersmentioning
confidence: 48%
“…Indeed, the growth of the Slgt mutant was less affected by H 2 O 2 than that of the wild-type strain. Involvement of Lgt in oxidative stress has been reported for S. agalactiae (Bray et al, 2009), although in that study, the mutant appeared more sensitive to oxidative stress. Using RT-qPCR, we determined the expression of genes encoding particular lipoproteins [ef0063, ef0273, ef0577, ef0685, ef1234, ef1362, ef1534, ef2076 (efaA) and ef3082 (fatB)] during growth in GM17 supplemented with H 2 O 2 .…”
Section: Phenotypic Characterization Of the Slgt Mutantmentioning
confidence: 52%
See 1 more Smart Citation
“…However, in many low-GC Gram-positive pathogens, mutations in either lgt or lsp also led to impaired pathogenicity. This was the case in various pathogenic streptococcal species such as Streptococcus pneumoniae (21,22), Streptococcus agalactiae (23,24), Streptococcus pyogenes, and Streptococcus equi (25,26). In Listeria monocytogenes, the lgt mutant was impaired in invasion and intracellular survival, was markedly attenuated in a mouse infection model, was unable to induce TLR2-dependent activation of NF-B, and exhibited increased susceptibility to cationic peptides (27,28).…”
Section: Maturation Of Pre-lpp Is Crucial For Pathogenicity and Inflamentioning
confidence: 99%
“…Pilus protein gbs80-deficient, san1518-deficient, and gbs67-deficient mutants of S. agalactiae were generated by allelic replacement (24). The mutant for gbs80 was constructed in type Ia, III, V, and VII; san1518 was constructed in type Ia, III, and VII; and gbs67 was constructed in type V and VII.…”
Section: Generation Of Isogenic Mutants Of S Agalactiae By Allelic Rmentioning
confidence: 99%